2022
DOI: 10.1155/2022/8212370
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Status Quo of Criminal Responsibility for Aflatoxin Pollution in China: From the Perspective of Judgment Analysis

Abstract: With the development of the economy, the food safety problems caused by aflatoxin have become increasingly prominent. With regard to the control of aflatoxin pollution, the Chinese government has promulgated a series of legal documents on food safety related to aflatoxin pollution, such as the formulation of industry standards for allowable limits of aflatoxin and various penalties for violators. Although these measures have achieved good results to some extent, there are still many legal problems. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%